SIMBLUD as a Digital Solution for Financial Management by Non-Accounting Human Resources: A Qualitative Study at BLUD Community Health Centers in Bone Regency - Fitriza Rahma; Isyraq Shalihah; Syarifuddin Syarifuddin; Arifuddin Arifuddin; Andi Rahmatullah (Universitas Negeri Makassar, 2026)
The transformation of Community Health Centers (Puskesmas) into Regional Public Service Agencies (Badan Layanan Umum Daerah / BLUD) requires strengthened accountability and efficiency in financial management supported by digital systems. However, the limited competence of non-accounting human resources remains a major obstacle in operating financial information systems, including SIMBLUD. This study aims to examine the utilization of SIMBLUD and its evaluation from the perspective of external auditors conducting audits at BLUD Community Health Centers in Bone Regency. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews with auditors from Public Accounting Firms, audit document reviews, and documentation studies. The findings reveal that the implementation of SIMBLUD contributes to improved administrative orderliness, more accurate accrual-based transaction recording, and enhanced financial reporting quality. Nevertheless, auditors identified several major issues, particularly the limited accounting understanding among system users, errors in account classification, and inconsistencies between standard operating procedures (SOPs) and system workflows. In addition, organizational support, continuous training, and active managerial supervision were found to be critical determinants of successful SIMBLUD implementation. This study confirms that although SIMBLUD provides significant benefits, the effectiveness of its implementation largely depends on the quality of human resources and organizational governance.